Comparative efficiency of antibiotics and Aqueous Fresh Neem Leaf Extract on growth Performance, Apparent Nutrient Digestibility, Carcass Characteristics and Economics of Production of Broiler Chickens - Shaahu, D.T.; Uza, O.; Gege, B.M.; Awua, L.L. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
A study to evaluate growth performance, nutrient digestibility and economics of production of broiler chicks served aqueous fresh neem leaf extract (AFNLE) and antibiotics. 180   day-old broiler chicks were weighed and allotted to 5groups of 36 birds each; each group replicated thrice with 12 birds per replicate. Experimental groups T1 and T2 were administered 0% extract and antibiotic respectively while T3, T4 and T5 were given 0.2, 0.4 and 0.6% AFNLE, respectively in a Completely Randomized Design. Results on growth indices were not significant (P>0.05).Apparent DM, CP and CF digestibility were significantly influenced (P<0.05) while EE was not significantly (P>0.05) influenced by test ingredients. Birds served AFNLE had higher apparent DM digestibility. Birds served synthetic antibiotic and AFNLE had highest and similar CP digestibility values (76.14) compared with birds on control group (70.50). Birds served antibiotics, 0.2 and 0.4% AFNLE had highest and similar CF digestibility values (76.14) compared to control and 0.6% AFNLE which had the least and similar values. Birds served antibiotics had the highest cost per feed consumed (₦943.31) and total production cost (₦1293.31) compared to birds served AFNLE. Birds served antibiotics, 0.2 and 0.4% AFNLE had highest gross profit compared to birds on control and 0.6% AFNLE. Carcass traits were generally unaffected however, relative pancreas weight decreased with increased concentration of AFNLE. It can be concluded that AFNLE at 0.2 and 0.4% had no deleterious effect on growth performance, increased profit margin, improved apparent CP and CF digestibility and carcass traits.